De-emulsification and gravity separation of micro-emulsion produced with enhanced oil recovery chemicals flooding - Khan, M.K.A. (MDPI AG, 2021)
The present study investigates the effect of TiO2 nanoparticles on the stability of Enhanced Oil Recovery (EOR)-produced stable emulsion. The chemical precipitation method is used to synthesize TiO2 nanoparticles, and their properties were determined using various analytical characterization techniques such as X-ray Diffraction (XRD), High-Resolution Transmission Electron Microscopy (HRTEM), and Field Emission Scanning Electron Microscopy (FESEM). The effect of TiO2 nanoparticles is evaluated by measuring oil/water (o/w) separation, rag layer formation, oil droplet size, and zeta potential of the residual EOR produced emulsion. The laser scattering technique is used to determine the o/w separation. The results showed that spherical-shaped anatase phase TiO2 nanoparticles were produced with an average particle size of 122 nm. The TiO2 nanoparticles had a positive effect on o/w separation and the clarity of the separated water. The separated aqueous phasesâ clarity is 75 and 45 with and without TiO2 nanoparticles, respectively. Laser scattering analysis revealed enhanced light transmission in the presence of TiO2 nanoparticles, suggesting higher o/w separation of the ASP-produced emulsion. The overall increase in the o/w separation was recorded to be 19 in the presence of TiO2 nanoparticles, indicating a decrease in the stability of ASP-produced emulsion. This decrease in the stability can be attributed to the improved coalescenceâ action between the adjacent oil droplets and improved behavior of o/w interfacial film. An observable difference was found between the oil droplet size before and after the addition of TiO2 nanoparticles, where the oil droplet size increased from 3 Âµm to 35 Âµm. A similar trend of zeta potential is also noticed in the presence of TiO2 nanoparticles. Zeta potential was â13 mV to â7 mV, which is in the unstable emulsion range. Overall, the o/w separation is enhanced by introducing TiO2 nanoparticles into ASP-produced stable emulsion. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.